Impact of Sky Conditions on The Performance of The Solar Still - Abdoul Aziz , Traore Damus; Boureima , Dianda; Hartwig , Combari Pagou; Kombassé, Bamogo; Rosina , Ouedraogo Maneg-Sanga Pélagie (International Journal of Engineering and Technology, 2025)
As part of improving the performance of active stills, we numerically studied the effects of sunlight on a concentrating still. ‎This is a double-slope solar still under which a parabolic trough concentrator was placed. We were particularly interested in the ‎impact of sky conditions on productivity, overall and internal efficiency, and exergy efficiency. Applying the energy balance ‎method to the different components of the still allowed us to calculate the productivity and the various efficiencies of the system. ‎Our system was simulated for the climatic conditions of the city of Ouagadougou (located at 12.35 North latitude and 1.32 ‎West) and for April. These results show that the nature of the sky has a significant impact on the operating ‎characteristics of the still. Indeed, the productivity, the overall, internal, and exergy efficiency of the distiller are a function of the ‎sunshine and therefore depend on the nature of the sky. These characteristics improve with the increase in sunshine. The best ‎operating characteristics are obtained for a clear sky because the sunshine is higher. We have a maximum overall radiation of ‎‎936.504 W/m² for a clear sky against 866.24 W/m² and 755.69 W/m² for a sky with normal atmospheric conditions and a ‎polluted sky. For a clear sky, we obtained a maximum productivity of 0.0014 kg/'s against 0.0011 kg/s and 0.0007 kg/s for a ‎sky with normal atmospheric conditions and for a polluted sky. It was concluded that productivity, the different efficiencies ‎are strongly affected by sunshine. The higher the radiation intensity, the better the productivity of the distiller‎.